Міжнародні спори щодо енергетичних ресурсів у практиці Міжнародного Суду ООН - Кориневич, А. О.; Кориневич, А. О.; Korinevich, А. (My University, 2011)
The article is dedicated to the analysis of the case-law of the International Court of Justice as to the energy resources. ICJ didn’t have too many cases which were connected to the questions of energy resources. ICJ and its predecessor – Permanent Court of International Justice, worked on two categories of cases connected with energy resources. PCIJ worked on energy concessions and ICJ – on oil and other energy resources.
Кориневич А. О. Міжнародні спори щодо енергетичних ресурсів у практиці Міжнародного Суду ООН / А. О. Кориневич // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. – Одеса : Фенікс, 2011. – Вип. 42. – С. 145 - 159.
Keywords: міжнародні спори; енергетичні ресурси; Міжнародний суд ООН; Міжнародне енергетичне право; международные споры; энергетические ресурсы; Международный Суд ООН; Международное энергетическое право; International energy law; International Court of Justice; power resources; international disputes